2015
DOI: 10.1007/s00784-015-1515-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional culture of dental pulp stem cells in direct contact to tricalcium silicate cements

Abstract: The tested new tricalcium silicate cement confirms its suitability as an alternative to MTA in vital pulp therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 46 publications
(72 reference statements)
7
60
0
6
Order By: Relevance
“…Results from the cytotoxicity assays after 4 days demonstrated significant DPSC viability when in contact with Biodentine as compared with the other groups. Our data are in consensus with Widbiller, et al 32 (2016) who showed that DPSC viability on MTA was significantly lower when compared with that of cells on Biodentine for the first seven days. Nevertheless, other studies have compared the cell viability of human pulp fibroblasts, human gingival fibroblasts, or osteoblast-like cells exposed to Biodentine or MTA and observed similar cell growth without statistically significant differences 2,13,14 .…”
Section: Discussionsupporting
confidence: 93%
“…Results from the cytotoxicity assays after 4 days demonstrated significant DPSC viability when in contact with Biodentine as compared with the other groups. Our data are in consensus with Widbiller, et al 32 (2016) who showed that DPSC viability on MTA was significantly lower when compared with that of cells on Biodentine for the first seven days. Nevertheless, other studies have compared the cell viability of human pulp fibroblasts, human gingival fibroblasts, or osteoblast-like cells exposed to Biodentine or MTA and observed similar cell growth without statistically significant differences 2,13,14 .…”
Section: Discussionsupporting
confidence: 93%
“…The influence of Biodentine ® and MTA on extracellular matrix proteins is versatile. It has been shown in a murine pulp cell line (OD21) [39] and human dental pulp cells [40] that calcium silicate containing materials decrease collagen type I mRNA expression [41, 42]. In our studies we could show that the described reduced collagen mRNA level correlates well with our collagen type I protein concentration analysis.…”
Section: Discussionsupporting
confidence: 85%
“…According to Widbiller et al . (), this may be attributed to a potential post‐transcriptional regulation; and a direct comparison is not possible, because of normalization of ALP activity on viable cell culture. It was also noticed that ALP gene expression was lower in the Biodentine group compared to the control group, which is inconsistent with most other studies (Bortoluzzi et al .…”
Section: Discussionmentioning
confidence: 99%